If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 4) = 6x + 26 Reorder the terms: 4(4 + x) = 6x + 26 (4 * 4 + x * 4) = 6x + 26 (16 + 4x) = 6x + 26 Reorder the terms: 16 + 4x = 26 + 6x Solving 16 + 4x = 26 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 16 + 4x + -6x = 26 + 6x + -6x Combine like terms: 4x + -6x = -2x 16 + -2x = 26 + 6x + -6x Combine like terms: 6x + -6x = 0 16 + -2x = 26 + 0 16 + -2x = 26 Add '-16' to each side of the equation. 16 + -16 + -2x = 26 + -16 Combine like terms: 16 + -16 = 0 0 + -2x = 26 + -16 -2x = 26 + -16 Combine like terms: 26 + -16 = 10 -2x = 10 Divide each side by '-2'. x = -5 Simplifying x = -5
| 4(6+8+x)= | | -7+7x=-1+7x | | -83+4x=8x+21 | | -2/-1.3 | | j=0+9 | | y=-16t^2+20t+120 | | 3x/4=-2/3 | | 1/4•3 | | -90-3x=-8x+30 | | 168=-v+62 | | 10h+3p= | | 24+12y-36x=O | | 3/5x-5/2=3/4x | | 4x-129=40-9x | | 6y+20=8x-10 | | 5e^7x-5=6 | | 2(X-3)+3x=26 | | 7+a=35 | | 11x-72=108-x | | 5(3x+1)-3(x-2)=10+5x | | 3+3y=2x-15 | | 16t^2+555=0 | | P-1/4•3=-5/6 | | -6x-80=9x+130 | | 8[x+5]=7[x+8] | | 6*(4*9-10)-6= | | 10=6x-x^2 | | -6x+80=9x+130 | | P=1/4•3=-5/6 | | 2x+24=10x+-72 | | 2x+24=2x-72 | | (13-8)*(12-3)+3= |